2020
DOI: 10.1183/13993003.04229-2020
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pulmonary arterial hypertension in adults carrying a BMPR2 mutation

Abstract: BackgroundHeritable pulmonary arterial hypertension (PAH) is most commonly due to heterozygous mutations of the BMPR2 gene. Based on expert consensus, guidelines recommend annual screening echocardiography in asymptomatic BMPR2 mutation carriers. The main objectives of this study were to evaluate characteristics of asymptomatic BMPR2 mutation carriers, assess their risk of occurrence of PAH, and detect PAH at an early stage in this high-risk population.MethodsAsymptomatic BMPR2 mutation carriers underwent scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 41 publications
0
48
1
6
Order By: Relevance
“…CPET is an attractive option for screening asymptomatic carriers since ventilatory abnormalities may be present early in the development of PAH, before echocardiographic changes suggesting PH are seen or when disease features begin to manifest [45,46]. The results of the DELPHI-2 study, which used a multimodal screening approach for asymptomatic BMPR2 mutation carriers, suggested that a CPET-derived probability score including the V′ E /V′ CO 2 can help detect early disease in this at-risk group [47].…”
Section: Is Ventilatory Inefficiency Useful In the Diagnosis Of Pulmonary Hypertension?mentioning
confidence: 99%
“…CPET is an attractive option for screening asymptomatic carriers since ventilatory abnormalities may be present early in the development of PAH, before echocardiographic changes suggesting PH are seen or when disease features begin to manifest [45,46]. The results of the DELPHI-2 study, which used a multimodal screening approach for asymptomatic BMPR2 mutation carriers, suggested that a CPET-derived probability score including the V′ E /V′ CO 2 can help detect early disease in this at-risk group [47].…”
Section: Is Ventilatory Inefficiency Useful In the Diagnosis Of Pulmonary Hypertension?mentioning
confidence: 99%
“…In this heterogenous but contemporary PAH cohort, we were able to confirm the predictive value of recognized clinical variables such as 6MWD, WHO functional class, and NT-proBNP levels [ 1 ], and additionally identify less established variables like renal impairment and DLCO as predictors for adverse outcome in PAH. Results from screening of susceptible subjects, both genetically or due to an underlying condition such as systemic sclerosis, further emphasize the importance of DLCO for early detection of pulmonary vascular disease [ 30 , 31 ]. Overall, our results support findings from the REVEAL-study and highlight the importance of comorbidities and pulmonary function testing in clinical evaluation [ 6 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our (re-)contact approach identified 10 relatives at risk as carriers and these carriers will be screened annually to detect PAH in early stages. Asymptomatic BMPR2 mutation carriers have a significant risk of 2.3% per year of developing PAH (0.99% per year in males and 3.5% per year in females) [11]. As shown in the DELPHI-2 study of Montani et al, annual screening of unaffected mutation carriers could be beneficial: annual screening identified five PAH cases and all patients remained at low risk with oral PAH-specific therapy during follow-up [11].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic BMPR2 mutation carriers have a significant risk of 2.3% per year of developing PAH (0.99% per year in males and 3.5% per year in females) [11]. As shown in the DELPHI-2 study of Montani et al, annual screening of unaffected mutation carriers could be beneficial: annual screening identified five PAH cases and all patients remained at low risk with oral PAH-specific therapy during follow-up [11]. These findings highlight the importance of detecting pathogenic variants in PAH patients and their relatives at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation